(untitled) (European Journal of Pure and Applied Mathematics, 2024)
In this paper, we study relations between inner products derived from the standard n-inner product defined on an inner product space. In particular, we are interested in knowing when orthogonality with respect to the original inner product is preserved by the derived inner product.